PERANAN GURU PENDIDIKAN AGAMA KRISTEN DALAM MEMBERIKAN BIMBINGAN KONSELING KEPADA SISWA KRISTEN DI SEKOLAH DASAR NEGERI SEMERU 1 BOGOR - Daeli, Dewi Rosiani; Lie, Romi (JURNAL KADESI, 2024)
This paper aims to find out how big the role of Christian Religious Education teachers is in providing counseling guidance to students in elementary schools. This research uses qualitative interview instruments. The data in this research were obtained from two homeroom teachers and two students. The results of the research show that: 1) Counseling guidance is very necessary and important to apply directly to students to help students complete their personal development tasks or solve the problems they are experiencing so they can grow as individuals who can actualize themselves, and can discover the potential that exists within themselves. 2) As a homeroom teacher, you must be able to act as a guidance and counseling teacher in guiding and accompanying students to solve their own problems. 3) The homeroom teacher, plus Christian Religious Education teachers and parents must work together to guide, accompany and help students find ways to resolve the obstacles they face in accordance with the skills and potential that exist within them. A Christian Religious Education Teacher is someone whose role is to bring students to grow in their introduction to the Christian faith. The teacher not only conveys knowledge to students but also plays the role of a counselor who will help every student who is having problems and assist students in finding solutions to the problems they face so that students can get out of the problems they are experiencing. In this research, it is hoped that Christian Religious Education Teachers will be aware and will implement counseling guidance in their calling to become a Christian Religious Education Teacher in every teaching place.